2020
DOI: 10.1136/jitc-2019-000326
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous inhibition of CXCR1/2, TGF-β, and PD-L1 remodels the tumor and its microenvironment to drive antitumor immunity

Abstract: BackgroundDespite the success of immune checkpoint blockade therapy in the treatment of certain cancer types, only a small percentage of patients with solid malignancies achieve a durable response. Consequently, there is a need to develop novel approaches that could overcome mechanisms of tumor resistance to checkpoint inhibition. Emerging evidence has implicated the phenomenon of cancer plasticity or acquisition of mesenchymal features by epithelial tumor cells, as an immune resistance mechanism.MethodsTwo so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 45 publications
(38 reference statements)
0
55
0
Order By: Relevance
“… 23 The expanding list of B7 family members includes CTLA-4 (ligands B7.1 and B7.2), PD-1 (ligands PD-L1 and PD-L2), TIM3 (ligands CEACAM-1, HMGB1 and galectin-9), TIGIT (ligands CD155 and CD112), BTLA (ligand HVEM), B7-H3, B7-H4 and VISTA. 24 25 In this study, we investigated the expression level of B7 family ligands/receptors in CPs. More importantly, we have discovered some associations between B7 family ligands/receptors expression and clinical features of CPs.…”
Section: Discussionmentioning
confidence: 99%
“… 23 The expanding list of B7 family members includes CTLA-4 (ligands B7.1 and B7.2), PD-1 (ligands PD-L1 and PD-L2), TIM3 (ligands CEACAM-1, HMGB1 and galectin-9), TIGIT (ligands CD155 and CD112), BTLA (ligand HVEM), B7-H3, B7-H4 and VISTA. 24 25 In this study, we investigated the expression level of B7 family ligands/receptors in CPs. More importantly, we have discovered some associations between B7 family ligands/receptors expression and clinical features of CPs.…”
Section: Discussionmentioning
confidence: 99%
“…The TgfβrII module was able to efficiently trap the Tgf-β1, -2 and -3 isoforms [145]. In murine breast and lung cancer models, treatment with bintrafusp alfa was combined with small molecule inhibitors targeting Cxcr1/2; the latter blocked interleukin 8 (IL-8) activity and thereby prevented the acquisition of mesenchymal properties by cancer cells [147]. This combination improved anti-tumour efficacy of either monotherapy, leading to decreased tumour volumes and increased infiltration of T and NK cells in the TME [147].…”
Section: Clinical Exploitation Of the Synergistic Potential Of Tgf-β mentioning
confidence: 99%
“…In an ongoing phase I clinical trial (NCT02517398), bintrafusp alfa has demonstrated good clinical response, safety, and tolerance in advanced head and neck squamous cell carcinoma (HNSCC) that progressed after platinum therapy [ 150 ]. In addition, a joint targeting of CXCR1/2, TGF-β1, and PD-L1 using the CXCR1/2 inhibitor SX-682 and bintrafusp alfa also reduces EMT, enhances the infiltration of effector T cells and promotes the blockade of granulocytic myeloid cells in breast and lung cancer mouse models in vivo [ 151 ]. Similarly, bifunctional fusion antibodies that simultaneously target the immune checkpoint and disable TGF-β signalling can significantly enhance the efficacy of cancer immunotherapy [ 152 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%